Pengaruh Bauran Pemasaran Jasa Terhadap Keputusan Penggunaan Jasa Transportasi Online Aplikasi Grab Berbasis Android Di Kota Samarinda - Taghfirul Azhima Yoga Siswa3, Muhammad Darmawan Eddy Soegiarto (EKONOMIA, 2020)
The purpose of this study was to determine the effect of the service marketing mix which includes product, price, place, promotion, people, process and physical evidence on the decision to use online transportation services based on Android Grab Application in Samarinda City.The theory used in this study is the service marketing mix and service use decisions. This research was conducted on Grab service users in Samarinda City. The population in this study is unknown and the sample taken was 78 respondents with the accidently sampling method. Data collection is done by distributing online questionnaires from the google forms using the Likert scale to measure each indicator. The analytical tool used is multiple linear regression.The results of the research on the f test show that the service marketing mix variables which include product, price, place, promotion, people, process and physical evidence have a joint effect on the decision to use services. The t test shows that the price, process and physical evidence variables have a significant effect on service use decisions while in the product, place, promotion and people variables there is no significant effect on the decision to use android-based online Grab Application transportation services in Samarinda City